The Analysis of UB Guest House Management towards University of Brawijaya Changing Status into Public Service Agency (Badan Layanan Umum) - Cuikitalia Cuikitalia; Fadillah Amin; Farida Nurani (Sekolah Pascasarjana Universitas Brawijaya, 2020)
The aim of this research is to analyze the management of UB Guest House towards University of Brawijaya changing status into Public Sercive Agency based on Good Corporate Governance perspective either for its implication strategy in enhancing UB Guest House revenue. The research method used in this research is qualitative with direct observation and interview. The informants of this research are management, staff, and UB Guest House’s guests. The result shows that the changing status of the University of Brawijaya has its pros and cons. Because of the changing status, UB Guest House as part of the University of Brawijaya, doing several changes such as ownership status, employees status, procurement, financial report, maximize cooperation, and management are authorized. With all those implications faced by UB Guest House, it is better if UB Guest House separated from the main office (in this case rectorate) and cooperate with alumni network all around Indonesia or international. This plan will make UB Guest House raise its revenue and compete with other competitors in the same field.